Early Developmental Trends in High-Risk Neonates Later Diagnosed With Autism Spectrum Disorder. Issue 1 (12th September 2022) - Carey, Helen; Tanner, Kelly; Ratliff-Schaub, Karen; Baldino, Maria; Kelly, Nicholas; Andridge, Rebecca R.
Abstract : Purpose: We hypothesized that clinical data from a neonatal intensive care unit (NICU) infant developmental follow-up clinic would identify early manifestations of autism spectrum disorder (ASD). Methods: One hundred forty-four infants were identified; 72 later diagnosed with ASD and 72 controls. Retrospective chart review provided data from the Test of Infant Motor Performance (TIMP) and the Bayley Scales of Infant and Toddler Development, third edition (Bayley-III), between 8 and 26 months of age. Results: Between-group comparisons indicated no significant group difference in TIMP scores; however, Bayley-III scaled scores differed between the groups at 2 administration times. The within-group Bayley-III change scores declined significantly more for the ASD group in cognitive and communication subtests. Conclusion: High-risk neonates, due to prematurity or morbidity, later diagnosed with ASD demonstrated statistically significant differences, including a more precipitous drop in Bayley-III scores over time. Early, longitudinal developmental surveillance for neonates at risk of ASD is critical. What this adds to the evidence: Early identification of ASD is critical to optimize developmental outcomes in young children, including infants born prematurely or with neonatal morbidity, who are perceived to have an increased risk for ASD. Despite these findings, minimal research has been conducted to evaluate the utility of commonly administered norm-referenced developmental surveillance instruments to identify possible early signs of ASD in this high-risk population due to prematurity or neonatal morbidity and not familial association. The present study analyzed retrospectively collected clinical data from a NICU developmental follow-up clinic for 144 infants, 72 of which were later diagnosed with ASD and 72 sex- and gestational age-matched controls. Results demonstrated statistically significant poorer Bayley-III outcomes for the ASD group compared with controls at 2 different study time points, including a more precipitous drop in Bayley-III scaled scores over time. This study highlights the importance of early and longitudinal developmental surveillance for high-risk neonates at risk of ASD.